Improving the Czech health care system - Fall, Falilou (OECD Economics Department Working Papers, 2018)
The Czech health care system is doing well in terms of health outcomes compared to other Central East European economies that inherited similar health systems after the transition and has been converging to OECD averages. However, benchmarking the Czech health system to countries with comparable institutional setting points to potential for efficiency gains. This paper assesses the performance and emerging key challenges of the Czech health system, and provides recommendations to adapt the system to remain effective and financially sustainable in the context of an ageing society. Further, the contribution of various disincentives in the system on the supply and the demand side of health care are discussed. This Working Paper relates to the 2018 OECD Economic Survey of Czech Republic. (www.oecd.org/eco/surveys/economic-survey-czech-republic.htm)